2013
DOI: 10.1097/mpa.0b013e31826bef91
|View full text |Cite
|
Sign up to set email alerts
|

Does Autoimmune Pancreatitis Increase the Risk of Pancreatic Carcinoma?

Abstract: These findings raise concern that AIP is associated with an elevated risk of malignancy and should prompt additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 21 publications
0
73
1
1
Order By: Relevance
“…Many patients are misdiagnosed initially as having adenocarcinoma of the pancreas -sometimes only after the performance of a modified pancreatectomy. Several cases of pancreatic cancer have been reported in patients with previous IgG4-related AIP, but a clear relationship between the two conditions still needs to be fully verified [23,24]. Secondary diabetes mellitus and malabsorption might complicate longstanding pancreatic disease.…”
Section: Overview Of Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients are misdiagnosed initially as having adenocarcinoma of the pancreas -sometimes only after the performance of a modified pancreatectomy. Several cases of pancreatic cancer have been reported in patients with previous IgG4-related AIP, but a clear relationship between the two conditions still needs to be fully verified [23,24]. Secondary diabetes mellitus and malabsorption might complicate longstanding pancreatic disease.…”
Section: Overview Of Clinical Manifestationsmentioning
confidence: 99%
“…Obstructive jaundice, diabetes mellitus, abdominal pain, pale stool, malabsorption Biliary tree/gallbladder [23,24] IgG4-related sclerosing cholangitis Jaundice, weight loss, abdominal pain Liver [24] IgG4-related hepatitis (hepatic inflammatory pseudotumour)…”
Section: Pathologymentioning
confidence: 99%
“…These findings suggest the possibility of a close association between AIP and pancreatobiliary cancer. Gupta et al [10] inspected resected pancreata to clarify the prevalence of pancreatic intraepithelial neoplasia (PanIN) in 28 cases of AIP, and identified that 23 cases (82 %) showed PanIN; grades 2 and 3 PanIN were demonstrated in 7 (25 %) cases and 1 case, respectively, thus strongly indicating an elevated risk of pancreatic malignancy.…”
Section: Aip and Pancreatobiliary Cancermentioning
confidence: 99%
“…[27][28][29][30] Cases of salivary duct carcinoma arising in the background of IgG4-associated sialadenitis and pancreatic carcinoma associated with autoimmune pancreatitis have also been reported. 31,32 In summary, the role of IgG4 in the pathogenesis of IgG4-related disease is currently unknown. Plasma cells in myeloma patients are mature immunocompetent cells that have undergone somatic hypermutation and class switch recombination.…”
mentioning
confidence: 99%